Synthesis, Characterization And Photophysical Studies On Chalcone-Based Chemosensors For The Detection Of Aluminium And Fluoride Ions - Chan, Yi Huan (2018)
In this thesis, the syntheses and studies of three different chalcone-based chemosensors for the detection of Al3+ and F–− ion by naked eye and fluorimetric method have been described. The structure elucidation for the ultimate compounds have been characterized by spectroscopic techniques (FT-IR, 1H- and 13C-NMR). The response of the receptor molecules to various metal ions and anions were investigated by UV-Vis and fluorescence spectroscopy methods and to some extend through naked-eye observations. Study on binding behavior of the synthesized chemosensor (1-[3-(2-Hydroxy-phenyl)-3-oxo-propenyl]-naphthalen-2-yloxy)-acetic acid (NAC) by UV-Vis spectrophotometer has shown excellent selectivity and rapid response toward Al3+ ion. The obvious fluorescence increment upon the addition of Al3+ ion over other metal ions made it a suitable selective chemosensor for Al3+ ion. Receptor NAC displays a change in absorption from 399 nm to 416 nm as the binding of NAC with Al3+ triggered the improvement in the rigidity of the system through the operation of chelation enhanced fluorescence (CHEF) which did not happen to other metal cations. The stochiometry of receptor NAC and Al3+ ion was found to be 2:1 using Job’s method with an association constant of Ka= 0.21×102 M-2. The shift in FT-NMR spectral data reveals that two O atoms of carboxyl and hydroxyl groups and the oxygen atom of the oxymethylene group involved in coordination. The receptor (1-[3-Oxo-3-(3-oxo-3H-benzo[f]chromen-2-yl)-propenyl] -naphthalen-2-yloxy)-acetic acid (CAC) detect Al3+ ion in 100% water medium in which a change in colour from yellow to cyan can be observed by naked eye. After the addition of Al3+ ion, the internal charge transfer (ICT) mechanism in coumarin chromophore was enhanced that can clearly be identified by naked eye. The 2:1 stoichiometry of receptor CAC:Al3+ ion was investigated by Job’s plot and the association constant was found to be Ka = 5.91 M-2. The anion sensing behaviours of 7-Diethylamino-3-[3-(2-hydroxy-naphthalen-1-yl)-acryloyl]-chromen-2-one (DNAC) were studied by UV-Vis technique. The formation of hydrogen bonding between the probe DNAC and F– ion gave rise to the increase in the emission intensity of probe at 524 nm which can be attributed to the internal charge transfer (ICT) developed by the deprotonation of OH from napthol unit to the chalcone moiety in the probe DNAC. There was no interference by other anions in the fluorescence intensity of the complex during the F– ion detection in CH3CN. Job’s plot suggests the ratio of DNAC: F– ion as 1:1 with an association constant of Ka=3.33×10-5 M-1.